Rare causes of emesis - Popa, Stefan L.; Chiarioni, Giuseppe; David, Liliana; Golea, George I.; Dumitrascu, Dan L. (Medicine and Pharmacy Reports, 2020)
Prompt diagnosis in the emergency department in the case of a patient with emesis may be difficult due to the increasing prevalence of diseases which manifest with emesis. Furthermore, in the case of chronic symptomatology, management and therapy are even more complicated. One episode of emesis rarely causes complications, but severe or repetitive episodes of emesis can cause life-threatening complications. For this reason, the diagnosis of the underlying disease which manifests with emesis is mandatory to be established in a short time in order to choose the correct therapeutic option. In order to systemize the process of diagnosis, this clinical narrative review will discuss only rare causes of emesis.